Language Style Used by the Main Character in Extremely Loud and Incredible Close Movie (2011) - Renita Mawarni; Ana Widiyanti (Metaphor, 2020)
There are three problems discussed in this research, those are; What types of language style used by the main character in Extremely Loud and Incredibly Close movie, what the function of language style used by the main character in Extremely Loud and Incredibly Close movie and what factors that influence the main character to use language style in Extremely Loud and Incredibly Close movie. The object of the research is the main character's utterance taken from a movie entitled Extremely Loud and Incredibly Close by Stephen Daldry. The method applied in this research is qualitative method because the researcher only gives description and explanation related to the data. The result shows that there are five type of language style and four functions of language style used by the main character as well as the factor influences described by Hymes theory can be found in the movie. The most type of language style used by the main character is consultative style. While the most function used by the main character is referential function.